Towards Sustainable Islamic Financial Inclusion: Integrating the Regulatory Framework of Islamic Banking and Islamic Microfinance Institutions in Indonesia - Hasan Sultoni; Fatkhur Rohman Albanjari; Reorycha Risma Putri; Stevia Ramadhani (Musyarakah: Journal of Sharia Economic (MJSE), 2026)
Introduction/Main Objectives: This study aims to analyze the regulatory dynamics of Islamic banking and Islamic microfinance institutions (IMFIs) in Indonesia and to formulate a regulatory integration model that supports Islamic financial inclusion. Background Problems: This topic is important because the rapid development of the Islamic financial industry has not been accompanied by adequate regulatory harmonization, thereby hindering the establishment of an integrated and inclusive Islamic financial system. Novelty: This study offers novelty by proposing a regulatory integration model based on institutional harmonization, regulatory synchronization, and integrated supervision, which has rarely been discussed comprehensively in previous studies. Research Methods: This research employs a normative legal method with a qualitative approach through library research. The data were collected from laws and regulations, academic literature, and related documents, which were analyzed using statutory, conceptual, and comparative approaches. The analytical framework is based on financial regulation theory and the maqashid sharia perspective emphasizing wealth protection, justice, and public welfare. Findings/Results: The findings reveal that Islamic banking operates under a more centralized and standardized regulatory framework supervised by the Financial Services Authority, while IMFIs are governed by a more complex and fragmented regulatory regime. This condition creates inconsistencies in supervision, prudential standards, Sharia compliance, and consumer protection, which contribute to the low level of Islamic financial inclusion. Conclusion: This study concludes that regulatory integration through institutional harmonization, regulatory synchronization, and strengthened integrated supervision is necessary to establish a more coherent, equitable, and inclusive Islamic financial system and to improve public access to Islamic financial services.